Filtering characteristics of parallel-connected fixed capacitors in LCC-HVDC considering the variations of system strength - Yang, Conghuan; Zhang, Qingtao; Zhao, Zhiyi (Frontiers in Energy Research, 2024)
The AC power system strength exhibits time-varying characteristics during operation, thereby affecting the filtering performance of filters in the system. Failure to account for this variability may result in the harmonic levels exceeding permissible limits under specific power system strength, thereby affecting the normal operation of the power system. Consequently, building upon the existing filtering technique based on parallel-connected fixed capacitors for LCC-HVDC systems, a method for tuning the parameters of parallel-connected capacitors is proposed, thereby the capacitance range meets the filtering requirements under various system strengths.